Penerapan Metode PBL untuk Meningkatkan Kemampuan Berpikir Kritis Fase E di Smak Seminari Mario John Boen Pangkalpinang - Maria Margaritha de Lellis Priyati Dua Ploe; Hartutik Hartutik; Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
At SMAK Seminari Mario John Boen, students' critical reasoning and cognitive abilities were found to be underdeveloped due to conventional, lecture-based teaching methods that lacked creativity and student involvement. This study aimed to enhance students' critical reasoning through the implementation of the Problem-Based Learning (PBL) method, which promotes creative and student-centered learning. Conducted as Classroom Action Research, the study involved 25 students in class X, phase E, and was carried out over two cycles, each consisting of four stages: planning, implementation, evaluation, and reflection. The PBL approach was applied to the Holy Trinity subject matter, with a focus on the critical reasoning dimension of the Pancasila Student Profile (P3), targeting the development of both cognitive and affective domains. Data were analyzed descriptively. The findings revealed a significant improvement in the affective aspect of critical reasoning, increasing from 56.67 in cycle 1 to 69.33 in cycle 2. Similarly, cognitive scores rose from 60.12 to 75.72. Achievement levels showed that 28% of students reached the Advanced stage, 48% the Proficient stage, 16% the Adequate stage, and 8% remained Undeveloped. Reflection results suggest the need for continued support in the affective domain. Overall, the research concludes that the Problem-Based Learning method, when aligned with the critical reasoning component of Pancasila Student Profile, effectively improves student learning outcomes both cognitively and affectively.